2004
DOI: 10.4028/www.scientific.net/msf.467-470.853
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Recrystallization in Grain-Oriented Silicon Steel

Abstract: Mechanism of Goss secondary recrystallization in grain-oriented silicon steel has been investigated by temperature gradient annealing and by in situ observation utilizing synchrotron x-ray topography. The results support the selective growth theory. Migration of Goss grains is controlled by second phase particles (inhibitor) and sharper Goss grains, which have higher frequency of CSL boundaries to the matrix, start to grow preferentially while the other matrix grains are stagnated by inhibitor. CSL boundaries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Harase et al [2] and Ushigami et al [3] emphasized that coincidence site lattice (CSL) boundaries play a key role during AGG and that Goss grains have a large fraction of grain boundaries with CSL relations. Also, Homma et al [4] suggested that AE9 boundaries with low energy are less frequently occupied by precipitates because of weak Zener pinning and have a high mobility compared with other general boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Harase et al [2] and Ushigami et al [3] emphasized that coincidence site lattice (CSL) boundaries play a key role during AGG and that Goss grains have a large fraction of grain boundaries with CSL relations. Also, Homma et al [4] suggested that AE9 boundaries with low energy are less frequently occupied by precipitates because of weak Zener pinning and have a high mobility compared with other general boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, the growth advantage for AGG has been approached mainly based on the assumption that the abnormally growing grain should exclusively have high-mobility boundaries, whereas the other grains should have relatively low-mobility boundaries. [2][3][4] However, misorientation analyses of the abnormally growing grain and the other grains using electron-backscattered diffraction (EBSD) do not support this assumption. [5][6][7] Furthermore, Hwang et al [7][8][9][10] has suggested the solidstate wetting mechanism for AGG, where the growth advantage of abnormally growing grains is approached in terms of grain-boundary energy.…”
Section: Introductionmentioning
confidence: 99%
“…CSL boundaries, especially ∑9 boundaries, are believed to have somewhat lower energies than general high angle boundaries and so are less strongly inhibited by Zener drag. These ∑9 boundaries occur relatively frequently for Goss grains existing in certain types of primary texture and are considered to confer the necessary mobility advantage 24,25) . HEGB model demonstrated that the role of the high-energy boundary is important in the late stage of secondary recrystallization when large Goss grains consume matrix grains 26,27) .…”
Section: Texture Evolution During the Temperature Rising Pro-mentioning
confidence: 99%
“…For the oriented silicon steels, various mechanisms of the development of secondary recrystallization have been already proposed. The CSL model and the HEGB model are frequently used to quantify the grain boundary characteristics in Goss textured silicon steel during AGG [24][25][26][27] . CSL boundaries, especially ∑9 boundaries, are believed to have somewhat lower energies than general high angle boundaries and so are less strongly inhibited by Zener drag.…”
Section: Texture Evolution During the Temperature Rising Pro-mentioning
confidence: 99%